Investigation on sleep-related cognition of Chinese health care workers during the first wave of COVID-19 pandemic - Wang, Wei; Ji, Xincan; Guo, Hao-Yang; Tao, Mengjun; Jin, Lairun; Chen, Miao; Yuan, Hui; Peng, Hui (Frontiers in Psychiatry, 2023)
Background The COVID pandemic has brought tremendous negative effects on the mental health of health care workers, such as anxiety, depression, and sleep disorders. We conducted this study to evaluate the sleep-related cognition of Chinese health care workers (HCWs) during the first wave of COVID-19 pandemic and analyze its association with sleep quality, so as to provide scientific reference for improving sleep of HCWs. Patients and methods A total of 404 HCWs from Yijishan Hospital of Wuhu City, China were enrolled in the study, selected by randomized cluster sampling in May 2020. We made a questionnaire to collect the general demographic information of the participants. The Pittsburgh Sleep Quality Index (PSQI) and a brief version of Dysfunctional Beliefs and Attitudes about Sleep Scale (DBAS-16) were used to measure sleep quality and sleep-related cognition, respectively. Results The results showed that 312 HCWs (77.2%) had false beliefs and attitudes about sleep, while only 92 HCWs (22.8%) had correct beliefs about sleep. In addition, we found that those HCWs who were older, married, with a bachelor’s degree or higher, nurses, more daily working hours (> 8 h) and monthly night shifts (≥ 5 times), had higher DBAS-16 scores (all p < 0.05). However, we did not find significant differences between men and women in DBAS-16 scores. According to the definition of PSQI, a total of 1/4 of the HCWs are poor sleepers and their DBAS-16 score was higher than good sleepers (t = 7.622, p < 0.001). In the end, we confirmed a positive correlation between sleep cognition and sleep quality (r = 0.392, p < 0.01). Conclusion Our study revealed false beliefs and attitudes about sleep were prevalent among HCWs during the first wave of COVID-19 pandemic, and these false beliefs about sleep were closely correlated to sleep quality. We recommend fighting against these false beliefs about sleep.